2016
DOI: 10.3389/fphys.2016.00565
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mRNA and MicroRNA Profiling during Acute Myocardial Infarction Induced by Coronary Occlusion and Ablation Radio-Frequency Currents

Abstract: The ligation of the left anterior descending coronary artery is the most commonly used experimental model to induce myocardial infarction (MI) in rodents. A high mortality in the acute phase and the heterogeneity of the size of the MI obtained are drawbacks recognized in this model. In an attempt to solve the problem, our group recently developed a new MI experimental model which is based on application of myocardial ablation radio-frequency currents (AB-RF) that yielded MI with homogeneous sizes and significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 102 publications
(118 reference statements)
1
15
0
Order By: Relevance
“…AMI is a major cause of morbidity and mortality worldwide and needs to be addressed urgently [ 12 ]. Apoptosis and necrosis are 2 pivotal events of AMI, which are known to play important roles during the process [ 13 , 14 ]. Myocardial apoptosis is followed by necrosis, which occurs during sustained and severe ischemia, and it is an unregulated irreversible response to a fatal challenge which usually involves myocardial pump failure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMI is a major cause of morbidity and mortality worldwide and needs to be addressed urgently [ 12 ]. Apoptosis and necrosis are 2 pivotal events of AMI, which are known to play important roles during the process [ 13 , 14 ]. Myocardial apoptosis is followed by necrosis, which occurs during sustained and severe ischemia, and it is an unregulated irreversible response to a fatal challenge which usually involves myocardial pump failure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are involved in the transcriptional and translational outcomes that coordinate these processes, such as regulation of size and function of the cardiomyocytes. MiRNAs also regulate cardiac contractility, Ca 2+ kinetics, ventricular wall integrity, angiogenesis, and cardiac remodeling [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al combined miRNA and mRNA sequencing to identify the protective transcriptome signature of enhanced PI3K signaling in the context of pathological hypertrophy; the results demonstrated that regulation of TGF/miR-21 contributed to the protection of enhanced PI3K signaling against cardiac hypertrophy [ 12 ]. Santana et al compared mRNA and miRNA expression profiles to identify transcriptional and post-transcriptional changes in AMI [ 13 ]. Moreover, a network-based method is an effective approach to globally identify biomarkers of disease.…”
Section: Introductionmentioning
confidence: 99%